The doctrine of Swart Gevaar to the doctrine of common purpose: a constitutional and principled challenge to participation in a crime - Davidson, Yusha (Department of Public Law, 2018)
Swart gevaar was a term used during apartheid to refer to the perceived security threat of the majority black African population to the white South African government and the white minority population. The Native Territories Penal Code, transported from English law, assimilated the doctrine of common purpose into South African law. During apartheid, the doctrine of common purpose served as one of many governmental tools to criminalise the black population and curtail the swart gevaar. The development of the doctrine largely occurred during the apartheid-era, whereby the white-ruled judiciary continuously sacrificed legal principles to ensure that the doctrine achieved its' crime control objective. The doctrine was expanded beyond its original scope in the Native Territories Penal Code to encompass two distinct forms of common purpose, namely: common purpose by prior agreement, whether by express or implied mandate; and common purpose in its active association form. In the 2003 case of Thebus and Another v The State, the Constitutional Court declared the doctrine of common purpose; in its active association form, constitutional. The Constitutional Court rejected the appellants' argument that the doctrine infringes an accused's constitutionally protected rights to dignity, freedom and security of persons, and a fair trial including the right to be presumed innocent. The Constitutional Court's finding came as a surprise, as it ignored worldwide condemnation of the doctrine throughout the apartheid regime and Constitutional democratic era. This paper challenges the Constitutional Court's finding and critically examines the doctrine of common purpose in the context of constitutional jurisprudence, general principles of criminal law, and policy considerations.